Penerapan Digital Marketing pada UMKM Keripik Pedas Ibu Iyar Kabupaten Rokan Hilir - Muhammad Rifqi; Larbiel Hadi; Bustami; Nofiar.Am, Andri; M. Alkadri Perdana (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
Spicy chips are the flagship product of the MSMEs Keripik Pedas Ibu Iyar, marketed both offline and online with the support of digital marketing strategies. The implementation of digital marketing has proven effective in increasing sales; therefore, this project aims to analyze the application of the strategy, including the challenges and solutions encountered. The MSMEs utilizes Instagram Business and Shopee as platforms for promotion, sales, and customer communication. The results show a significant increase in revenue and market reach to various regions. Active use of social media also helps strengthen brand awareness and attract new customers. However, several challenges remain, such as unstable internet connections, limited human resources, lack of social media management skills, and intense competition among MSMEs in the digital marketplace. The proposed solutions include basic digital marketing training, capacity building for human resources, and optimizing creative and consistent promotional strategies to maintain business competitiveness.